Efektivitas Penerapan Discharge Planning pada Pasien Diabetes Melitus untuk Meningkatkan Kesiapan Pulang Pasien di Ruang Cempaka RSUD Bali Mandara : Studi Kasus - Dwi Nanda Pratiwi; Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum; Gede Darmawan Puthro (KHD Production, 2024)
Diabetes mellitus sufferers experience disturbances in the system of regulating blood sugar levels, insulin is not sufficient to cope so that blood sugar levels increase. This causes patients to require long-term care, so they must be given discharge planning. This research aims to analyze the effectiveness of implementing discharge planning in diabetes mellitus patients to increase patient readiness to go home in the Cempaka Room at Bali Mandara Hospital. The research method used univariate descriptive analysis, and the sample used was in accordance with predetermined inclusion and exclusion criteria and then one respondent was selected. The research results showed that a 61-year-old patient with a diagnosis of diabetes mellitus who met the criteria was given discharge planning and measured using the adult Indonesian version of the patient discharge readiness scale instrument. The pre-test results showed that the patient's readiness level for discharge was 49.52% with a total score of 104 (level II). After implementing discharge planning, the level of patient readiness for discharge increased to 64.28% with a total score of 135 (level III). The implementation of patient discharge planning has proven to be effective in increasing patient discharge readiness, as evidenced by an increase in patient discharge readiness from level II to level III. Therefore, in providing nursing care, it is necessary to pay attention to the patient's detailed needs and fulfill them by implementing discharge planning so that patients have a good level of readiness to go home to reduce recurrence, complications, and patient readmissions.